The requirement of accessibility: European automated border control systems for persons with disabilities. (February 2018) - Oostveen, Anne-Marie; Lehtonen, Pinja
Abstract: This exploratory study investigates whether automated border control systems should be provided for persons with disabilities at European airports. While the special assistance provided to disabled passengers has improved in the last decade, some may want to travel independently using automated gates. This is currently not possible, nor is there an explicit plan to include the accessibility requirement in future technology development. We reflect this questionable situation against the notion of the good society and consider airports as normatively laden socio-physical zones contributing to experiences of exclusion. Our research stresses the need to consider human abilities as a spectrum, which should be addressed with the use of universal design principles to benefit as many travelers as possible. Interviews and a survey of disabled passengers help us explore the views of stakeholders; to find out whether persons with disabilities wish to use automated systems instead of assistance services, and whether stakeholders consider accessible systems technologically possible, cost-effective, and recommendable. Highlights: Independent travel for passengers with disabilities using automated border control (ABC) is currently not possible. Accessible ABC systems would ensure equal freedom of choice and benefit large segments of the European population. Accessible e-gates appear possible from the operational, technological, and economic perspective. People with a disability should be involved in the design of ABC systems. EU legislation should be created that makes universal design a regulatory requirement in the tendering processes.